Phenotypic changes in the body of black seabream, Spondyliosoma cantharus (Teleostei: Sparidae), along the eastern Atlantic. (15th December 2018) - Neves, Ana; Vieira, Ana Rita; Sequeira, Vera; Paiva, Rafaela Barros; Gordo, Leonel Serrano
Abstract: Knowledge of population spatial structure is essential in fisheries management. The study of morphological variation patterns in fishes can indicate differences in growth and maturation rates, and thus provide information on group dynamics that should be modelled and managed separately. Identification of intraspecific groups which have different life history features is necessary for understanding population dynamics and achieving a sustainable harvest. The black seabream, Spondyliosoma cantharus, has an extensive distribution along the eastern Atlantic Ocean and is an important commercial fish, exploited in European waters by recreational and commercial fishers. In this paper, body geometric morphometrics was used in order to discriminate among black seabream geographical populations caught in seven different geographical areas. The results showed the existence of intraspecific groups of black seabream across the eastern Atlantic Ocean, with Canary and Angola having clear distinct morphotypes and at least four populations in the European Coast (English Channel, Galicia, Peniche and Algarve) that present stable body shape differences. These populations should be considered to be separate and studies on life history parameters should be enhanced and updated.